Inclusive Madrasas in Central Java Indonesia: Culture, Policy, and Practices - Hakiman; Khuriyah; Siti Choiriyah (DINIKA : Academic Journal of Islamic Studies, 2022)
This study aims to explore the implementation of inclusive education in inclusive madrasas, particularly madrasah ibtidaiyah, in Central Java, Indonesia. Four inclusive madrasas were involved, namely: Madrasah Ibtidaiyah Muhammadiyah Kartasuro Sukoharjo, Madrasah Ibtidaiyah Keji Ungaran Semarang Regency, Madrasah Ibtidaiyah Ma'arif Sidomulyo, and Madrasah Ibtidaiyah Salafiyah Kebumen. As qualitative research, several techniques were employed to collect data, including observation, interviews, forum group discussion, and documentation. The interviews with policy makers, school principals, vice principals, teachers, and inclusive education teams were carried out. This article argues that inclusive schools are implemented based on the three pillars, namely culture, policy, and practices. An inclusive school culture is manifested in the provision of inclusive education services. The inclusive policies are manifested in the vision, mission, and featured programs supported by the capacity development for the treatment of children with disabilities. The practices of inclusive education in madrasas entail the identification and assessment of children with disabilities, as well as the adaptation and accommodation of the curriculum. The inclusive instruction is equipped with individual learning program plans, integrated and modified methods, media, and assessment.